Supply and Demand Concerning Urban Green Spaces for Recreation by Elderlies Living in Care Facilities: The Role of Accessibility in an Explorative Case Study in Austria - Artmann, Martina; Mueller, Christian; Goetzlich, Lukas; Hof, Angela (Frontiers in Environmental Science, 2019)
Urban green spaces (UGS) are crucial providers of cultural ecosystem services such as recreation. So that urban residents can benefit from UGS recreation, there is a need for good access to these, in particular for elderlies with reduced mobility. Recent research on accessibility has often neglected to consider real distances to green spaces and emerging barriers as well as the demand by specific user groups for UGS accessibility. In the light of demographic ageing and ongoing urbanization, this study investigates in an explorative case study the potential and actual access to UGS for elderlies living in care facilities in Salzburg (Austria). By connecting a GIS network-analysis with a survey among elderlies of four care facilities, the results give insights into the supply and demand concerning UGS accessibility. The supply analysis showed that the majority of UGS are situated between 500-1,000m. Due to barriers identified by the elderlies hindering the pathways to the UGS, time losses occur and the security of the old-aged is under risk. The demand side showed that despite the supply of UGS within 1,000m, elderlies mostly visit UGS outside the service area. More research is needed to include elderlies´ supply and demand regarding UGS qualities when analyzing UGS accessibility by considering greater sample sizes.